Skill formation in Central and Eastern Europe : a search for patterns and directions of development - Tutlys, Vidmantas [Herausgeber]; Markowitsch, Jörg [Herausgeber]; Winterton, Jonathan [Herausgeber]; Pavlin, Samo [Herausgeber] (Peter Lang, 2022)
"'Skill formation in Central and Eastern Europe' offers holistic analytical insight into skill formation processes and institutions in Central and Eastern European countries by referring to the timeframe of historical development of skill formation from the fall of communism to the present time and future development trends. Leading researchers of skill formation from Lithuania, Latvia, Estonia, Poland, the Czech Republic, Slovakia, Hungary, Slovenia, Croatia, Bulgaria, Romania and Ukraine refer to critical junctures and the findings are compared and discussed in five concluding chapters focused on important cross-cutting topics: development of social dialogue over skill formation, qualifications policy and development of qualifications systems, implications of European integration and EU policies for governance and institutional reform of skill formation, features and implications of policy borrowing and policy learning from the Anglo-Saxon and German speaking countries, respectively." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; G 1.2.3 Qualifikationsentwicklungen; I 2.2.2 Osteuropa; 370; Berufsbildungssystem; Qualifikation; Kompetenz; Kompetenzentwicklung; Qualifikationsforschung; Berufsbildungspolitik; Internationaler Vergleich; Bulgarien; Estland; Kroatien; Lettland; Litauen; Polen; Rumänien; Slowakei; Slowenien; Tschechische Republik; Ukraine; Ungarn